Oxytocin und Misshandlungspotenzial: Einfluss von mütterlicher Depression, Borderline-Persönlichkeitsstörung und frühkindlicher Misshandlungserfahrung - Kluczniok, Dorothea; Herpertz, Sabine (Der Nervenarzt, 2019)
BackgroundThe “empathy hormone” oxytocin (OXT) is associated with social interaction and parent-child interaction. Mothers with mental stress factors, e.g., history of depression, borderline personality disorder or early life maltreatment in their own childhood often show distinct maternal behavior.The objectives of the study were (1) to examine the association between these three stress factors and maternal OXT within one analysis. (2) Moreover, OXT was tested as a potential mediator for the association between maternal experience of early childhood maltreatment and abuse potential against their own child.MethodsPlasma OXT concentrations of 52 mothers during the follicular phase were collated (healthy control mothers n = 22, history of depression n = 23, borderline personality disorder n = 7). The maternal history of psychiatric disorders and experiences of early childhood maltreatment were examined via interviews. Regression and mediation analyses were applied to answer the research questions.ResultsEarly childhood maltreatment was associated with reduced plasma OXT; however, maternal history of depression and borderline personality disorder were not related to OXT concentrations. In particular, having experienced parental antipathy in one’s own childhood was associated with reduced OXT levels but OXT did not mediate the association between maternal early childhood experiences of maltreatment and abuse potential of their own child.ConclusionIn the present study alterations in plasma OXT concentrations were not associated with psychiatric disorders, such as a history of depression or borderline personality disorder but more with a potential etiological factor of these disorders, i.e. experience of maltreatment in their own childhood.
Online publiziert: 6. Februar 2019
Gesehen am 13.05.2019